ANALISIS DAMPAK PENGEMBANGAN WISATA PUNCAK KOTO PANJANG DALAM MENINGKATKAN PENDAPATAN PEDAGANG DI DESA LANSEK KADOK KABUPATEN PASAMAN MENURUT ETIKA BISNIS ISLAM - Alifatin Nurfaizah; Zuwardi Zuwardi (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This study was motivated by traders in the long Koto Puncak Koto area which is located at Puncak Koto-long Gotgarian Lansek Giftsk, Jorong II Koto-long, Pasaman Regency. And to find out Islamic Business Ethics in trading. Also knowing the Impact of The Peak Koto- long Tourism Development On Traders’ income. This type of research is qualitative research with a research approach used by norms and sociology. The primary sources of this research adalahdata are primary and secondary data. Data processing techniques and analysis techniques are carried out with Milles and Heubermen with three stages, namely: data reduction, data presentation, and drawing conclusions. From the research conducted on the field, it can be concluded that the Impact of Koto-long Tourism Development in Increasing Traders’ Revenue in Lansek Village of Gifts Pasaman Regency, according to Islamic Business Ethics with the Existence of Koto Long Tourism Objects has a big impact as a place that is able to absorb employment as well as the provision of the field among other people who are able to absorb labor. This is based on the results of the study conducted by studies that show a state after evidenced by the existence of the village community that became labor as a manager and merchant at the Peak coto-long Tourist Objects. The people of Lansek Giftul Village have many income from this job, and increase the results of income for the community, especially traders at the Long Koto Tourism Peak Area. Also still being found by the activities of traders who are not in accordance with the principles of Islamic Business Ethics, namely Atlas God SWT because merchants are only world-oriented and do not think about the hereafter. The intention of sincerity should be expected from Allah is the main thing in all businesses carried out during life in the world. But there are also traders who are in accordance with Islamic business ethics, which is honest and trust where the author finds facts in the field that traders at the top coto length are honest.